2020
DOI: 10.1039/d0me00036a
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring morphology of hierarchical catalysts for tuning pore diffusion behaviour: a rational guideline exploiting bench-top pulsed-field gradient (PFG) nuclear magnetic resonance (NMR)

Abstract: The aim of this work is to develop and quantify the tuning of transport properties in porous catalytic materials by tailoring their textural properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…For the measurements at 300 MHz the experiment showed a linear attenuation over two orders of signal decay. Such a result indicates a homogeneous sample, [12,22] with the liquid throughout the sample experiencing a uniform diffusion path over distances of the root mean square displacement of the experiment (2DptΔ ∼10 μm for a diffusion time of tΔ =100 ms). Diffusion heterogeneities on a longer length scale were not observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the measurements at 300 MHz the experiment showed a linear attenuation over two orders of signal decay. Such a result indicates a homogeneous sample, [12,22] with the liquid throughout the sample experiencing a uniform diffusion path over distances of the root mean square displacement of the experiment (2DptΔ ∼10 μm for a diffusion time of tΔ =100 ms). Diffusion heterogeneities on a longer length scale were not observed.…”
Section: Resultsmentioning
confidence: 99%
“…Typical experimental parameters (using the notation of Ref. [22]) were a gradient pulse duration t d = 1 ms, a diffusion time t D ¼150-170 ms, and t se of 2.7 ms. Typical APGSTE acquisition times were ~7 min.…”
Section: Chemistry-methodsmentioning
confidence: 99%
“…[ 25 ] Others have used benchtop PFG NMR experiments for the determination of the molar mass of lignins, [ 29 ] the hydrodynamic radii of PEE‐G dendrons [ 21 ] or for the characterisation of porous catalytic material. [ 11 ] The treating of benchtop PFG NMR data, however, is especially challenging, as the low resolution impedes accurate estimation of the peak intensities, which are needed for an accurate determination of the self‐diffusion coefficients. Assemat et al [ 1 ] reported the use of a benchtop NMR spectrometer to predict self‐diffusion coefficients from drug samples using univariate processing.…”
Section: Introductionmentioning
confidence: 99%
“…Pore diffusion behaviour was also explored with an aid of PFG NMR for hierarchical alumina, for which macropores were introduced to the mesoporous structures. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Pore diffusion behaviour was also explored with an aid of PFG NMR for hierarchical alumina, for which macropores were introduced to the mesoporous structures. 14 In this work, PFG NMR was used as a tool to determine diffusivity of n-hexadecane in H-MCM-41 powder and extrudate catalysts containing different amounts of Bindzil as a binder. PFG NMR experiments were performed using a stimulated echo pulse sequence with bipolar gradients.…”
Section: Introductionmentioning
confidence: 99%